Beyond Gender: Reflections on a Contemporary Case of Double Monastery in Orthodox Monasticism—St. John the Baptist Monastery of Essex in England - Maria Chiara Giorda (Religions, 2019)
This paper focuses on the contemporary controversy in the Orthodox Church regarding the non-existence of the monasteries, where monks and nuns cohabit (so-called “double-monasteries”), which were prohibited by the Byzantine legislation and the Seventh Ecumenical Council (Nicea 787). The article attempts to demonstrate that, in spite of the centuries-old prohibition, the Orthodox Monastery of St. John the Baptist is an exceptional contemporary case of such cohabitation: monks and nuns live under the roof of the same monastery, sharing common places and certain activities. Furthermore, the paper envisions a possible accommodation in the monastic vision and practice regarding gender cohabitation in Orthodox monasticism. The research employs the historical-critical method, which is based on literary, archeological, and documentary sources, as well as interviews.